Digitalisasi Mempengaruhi Kinerja Perusahaan: Peran dari Bisnis Model Inovasi (Evidence from Indonesia) - Karmilah, Karmilah; Hasnawati, Hasnawati; Wardhani, Nurhastuti Kesumo (Owner : Riset dan Jurnal Akuntansi, 2024)
Advances in digitalization provide various opportunities to innovate and create value. It is hoped that this research can be a reference for academics and practitioners that companies need to prioritize investment in digital assets and technology that are integrated in innovative business processes so that they can create value and improve company performance. This research aims to determine the influence of digital operations capabilities and digital integration capabilities through the role of business model innovation in improving company performance. This research method uses purposive sampling on industrial companies in 2020-2022 with 120 data with a panel data regression model. The research results show that digital operational capabilities, digital integration capabilities and efficient business model innovation are not able to mediate digital operational capabilities and company performance. However, the efficiency of the innovation business model is able to mediate the relationship between digital integration capabilities and company performance